2016
DOI: 10.1016/j.ejrad.2015.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Differences in morphological features and minimum apparent diffusion coefficient values among breast cancer subtypes using 3-tesla MRI

Abstract: Conclusion:Morphology and minimum ADC would be useful in distinguishing breast cancer subtypes. pg. 2 KeywordBreast cancer subtypes, Magnetic resonance imaging, Diffusion weighed imaging, pg. 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 19 publications
8
21
0
Order By: Relevance
“…Notably, HER2-positive cancer had significantly higher ADC 0 and sADC values than luminal B (HER2-negative) cancer. This difference was not observed in other group (19). There was a trend of smaller ADC 0 , sADC, and ADC values in luminal B (HER2-negative) cancer than in luminal A cancer, which was in agreement with the literature (19), although our observed trend did not reach the statistical difference after Bonferroni correction.…”
Section: Relationship Of Non-gaussian Dw Imaging and Ivim Parameters supporting
confidence: 91%
“…Notably, HER2-positive cancer had significantly higher ADC 0 and sADC values than luminal B (HER2-negative) cancer. This difference was not observed in other group (19). There was a trend of smaller ADC 0 , sADC, and ADC values in luminal B (HER2-negative) cancer than in luminal A cancer, which was in agreement with the literature (19), although our observed trend did not reach the statistical difference after Bonferroni correction.…”
Section: Relationship Of Non-gaussian Dw Imaging and Ivim Parameters supporting
confidence: 91%
“…The association of spiculated border characteristics with low grade, low Ki-67 index (<20%), and association of annular contrast enhancement with high histologic grade and ER/PR negative subtype were reported in the literature (10,11). Similarly, we demonstrated that spiculated border characteristics were associated with ER/PR positive cancers, particularly with luminal A subtype.…”
Section: Resultssupporting
confidence: 79%
“…The tumour ADC has been evaluated as a candidate biomarker for the prediction of responses to neoadjuvant chemotherapy, and has been used to make differential diagnoses between benign and malignant breast masses . Moreover, ADC has been utilized as an indicator of tumour aggressiveness, Ki‐67 expression, tumour cellularity and the expression of prognosis biomarkers in breast cancer . Recent studies have reported a correlation between ADC and the molecular markers of breast cancer .…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Moreover, ADC has been utilized as an indicator of tumour aggressiveness, Ki-67 expression, tumour cellularity and the expression of prognosis biomarkers in breast cancer. [19][20][21][22][23] Recent studies have reported a correlation between ADC and the molecular markers of breast cancer. [24][25][26][27] In addition to direct analysis of the entire tumour, DWI information on the breast tumour-stromal boundary and adjacent tissue surrounding the tumour has also been combined to associate DWI parameters with pathological factors or to predict responses to treatment.…”
mentioning
confidence: 99%